Navigating a Miniature Crawler Robot for Engineered Structure Inspection - Sheng, W; Chen, H; Xi, N (IEEE transactions on automation science and engineering, 2008)
This paper addresses the problem of how to navigate a miniature Crawler robot in a typical engineered structure inspection application-aircraft rivet inspection. First, a novel vision-assisted localization algorithm is developed to find the heading and position of the Crawler robot. Second, a new algorithm is developed to solve the path planning problem so that the Crawler robot can navigate through all the rivets. Experimental results validate the localization and path planning algorithms. This inspection system can be extended to other similar engineered structure inspection applications.